The impact of urban density on the form and function of public spaces in sustainable city planning - Sitiningrum, Diah Sabatini (Journal of Placemaking and Streetscape Design, 2024)
Background: This study examines the impact of population growth on land use changes in North Jakarta. As one of the rapidly developing coastal areas, North Jakarta has undergone significant transformations in land use patterns due to urbanization pressures and the increasing demand for residential, industrial, and infrastructure space. Methods: Based on data from the Central Bureau of Statistics (BPS) and previous literature studies, there was a substantial population increase from 2008 to 2018, accompanied by a dominant shift in land use from open spaces and agricultural land to built-up areas. Findings: Population growth has also led to intensive land conversion in strategic areas with direct access to key infrastructure, such as Tanjung Priok Port. Conclusion: This study suggests the implementation of more sustainable spatial planning to address environmental challenges and maintain the balance of the urban ecosystem. Novelty/Originality of This Study: This study provides a novel perspective by analyzing the spatial dynamics of land conversion in North Jakarta, highlighting the direct impact of population growth on strategic urban areas with key infrastructure access.